Evaluación técnico-financiera del consumo energético mediante nuevos diseños en los pozos completados con bombeo electrosumergible en campos operado pos parex (2020)
The current study evaluates a sample of twenty wells operating with electrical-submersible pumps as artificial lift systems and identifies those with high energy consumption and/or operational limitations, either because of the emulsion condition mentioned above or by some other specific operational condition in each well or the equipment each one has installed; with the intention of generating for these wells new designs of electrical-submersible pumping systems different from those currently installed, aiming to reduce energy consumptions (and therefore operational costs) or increasing production capacity. It is pursued to reduce energy consumptions through new designs, which would allow pumps to work at their best effiency region during their operation even with the presence of emulsions, increasing their operational life and saving electrical energy in the fields.